Autonomy rights and abortion after the point of viability. (18th August 2021) - Hine, Kristen
Abstract: It has been argued that Thomson's defense of abortion, if successful, implies that abortion is permissible only until the point of viability. After that point, if one wanted to end a pregnancy, one must do so by birthing the fetus through induction or cesarean. In this paper, I argue that Thomson's defense of abortion does, in fact, imply that abortion after the point of viability is sometimes permissible. To show this, I point out that the process of birthing a fetus makes use of the body of the pregnant person in significant ways. Indeed, the body of the pregnant person is as much a part of this process as it is a part of the process of carrying a fetus during pregnancy. Thus, just as it is sometimes morally permissible to choose to have an abortion rather than continue a pregnancy, it is sometimes morally permissible to choose to have an abortion rather than undergo an induction or cesarean. Those who support Thomson's defense of abortion, then, have reason not to support the view that induction or cesarean are the only permissible procedures for ending an unwanted pregnancy with a viable fetus. I then use this discussion to suggest that autonomy rights are more complicated than initially thought. Given the extent to which the body is involved in detaching the fetus, it is not merely that one has a right to detach a fetus, but also a right to actualize one's reasonable preferences over the method of detachment.